Translating Neuroscience into Counseling Practice - Goncalves, Oscar F.; Perrone-McGovern, Kristin M. (Canadian Journal of Counselling and Psychotherapy, 2016)
Recent advances in the field of cognitive neuroscience have led to a call for counsellors to translate new knowledge about brain-mind relationships into counselling practice. In this article, we address how counsellors can bring neuroscience into their practice with clients across developmental life stages, by utilizing interventions that promote positive brain plasticity (i.e., increased efficiency in brain structure, function, and connectivity) and reverse the effects of negative plasticity (i.e., decreased neural efficiency such as maladaptive necrosis or synaptic loss).